Colchicine-mediated selective autophagic degradation of HBV core proteins inhibits HBV replication and HBV-related hepatocellular carcinoma progression - Hui Zhang; Xiameng Su; Leirong Gu; Ming Tan; Yuting Liu; Kexin Xu; Jihua Ren; Juan Chen; Zhihong Li; Shengtao Cheng (Cell Death Discovery, 2024)
Abstract The HBV core protein (HBc) is an important viral protein of HBV that plays an indispensable role in the lifecycle of HBV, including capsid assembly and transport, reverse transcription and virus release. In recent years, evidence has shown that HBc may be involved in the malignant progression of HCC. Thus, HBc is an attractive target for antiviral agents and provides a new strategy for the treatment of HBV-related HCC. Here, we identified a novel anti‐HBc compound—colchicine, an alkaloid compound—that promoted selective autophagic degradation of HBc through the AMPK/mTOR/ULK1 signalling pathway. We further confirmed that colchicine promoted the selective autophagy of HBc by enhancing the binding of HBc to the autophagy receptor p62. Finally, we evaluated the effects of colchicine on HBV replication and HBc-mediated HCC metastasis in vitro and in vivo. Our research indicated that the inhibitory effects of colchicine on HBV and HBV-related HCC depend on the selective autophagic degradation of HBc. Thus, colchicine is not only a promising therapeutic strategy for chronic hepatitis B but also a new treatment for HBV-related HCC.